Fermented grape seed meal promotes broiler growth and reduces abdominal fat deposition through intestinal microorganisms - Nan, Shanshan; Yao, Min; Zhang, Xiaoyang; Wang, Hailiang; Li, Jiacheng; Niu, Junli; Chen, Cheng; Zhang, Wenju; Nie, Cunxi (Frontiers in Microbiology, 2022)
The fermentation of grape seed meal, a non-conventional feed resource, improves its conventional nutritional composition, and promotes the growth and development of livestock and fat metabolism by influencing the structure and diversity of intestinal bacteria. In this study, the nutritional components of grape seed meal fermented by bacteriase (FGSM) and their effects on the growth performance, carcass quality, serum biochemistry, and intestinal bacteria of yellow feather broilers were investigated. A total of 240 male 14-day-old yellow-feathered broilers were randomly selected and divided into four groups, with three replicates of 20 chickens each. Animals were fed diets containing 0% (Group I), 2% (Group II), 4% (Group III), or 6% (Group IV) FGSM until they were 56 days old. The results showed that Acid soluble protein (ASP) and Crude protein (CP) contents increased, Acid detergent fiber (ADF) and Neutral detergent fiber (NDF) contents decreased, and free amino acid content increased in the FGSM group. The non-targeted metabolome identified 29 differential metabolites in FGSM, including organic acids, polyunsaturated fatty acids, and monosaccharides. During the entire trial period, Average daily gain (ADG) increased and Feed conversion ratio（FCR) decreased in response to dietary FGSM supplementation (P<0.05). TP content in the serum increased and BUN content decreased in groups III and IV (P<0.05). Simultaneously, the serum TG content in group III and the abdominal fat rate in group IV were significantly reduced (P<0.05). The results of intestinal bacteria analysis showed that the addition of 4% and 6% FGSM significantly increased the Shannon and Simpson indices (35 d) of broilers (P<0.05), and the FGSM diet increased the relative abundance of Firmicutes but decreased the relative abundance of Bacteroidetes (P<0.05). At the age of 56 days, butyric acid content increased in the cecal samples from Group III (P<0.05). In addition, Spearman’s correlation analysis revealed a strong correlation between broiler growth performance, abdominal fat percentage, SCFAs, and gut microbes. In summary, the addition of appropriate levels of FGSM to rations improved broiler growth performance and reduced fat deposition by regulating gut microbes through differential metabolites and affecting the microbiota structure and SCFA content of the gut.